Geology and Ecosystems - Zektser, Igor S.; Marker, Brian; Ridgway, John; Rogachevskaya, Liliya; Vartanyan, Genrikh (Springer US : Imprint: Springer, 2006)
Geology and Ecosystems examines the relationship between biological communities of the Earth and objects of inorganic nature of the geological environment. Rational and sustainable development of society requires an ever-growing exploitation of natural resources, among which mineral and water resources play a dominant role. During recent decades, we have observed a high rate of human invasion into our geological structure, mainly through extraction of minerals, hydrocarbons, groundwater, etc. These impacts together with day-to-day human activity, cause destruction to the Earth's surface and near-surface environment and upset the balance of sustainable development. In turn, due to increasing anthropogenic impact, the geological components which serve as the basic substrate and foundations for all ecosystems, are changed from their natural original state and the relationship between the 'living tissue and inert nature' (i.e. relationship between the biosphere and the geosphere) is significantly affected. This book includes an analysis of the relationship between the different geological, hydrochemical, hydrogeological and engineering-geological processes and the processes within surface ecosystems. The analysis of specific interactions between the lithosphere and biosphere provides an integrated concept of the role of the geological environment in the evolution of the biosphere. The practical significance of the book is reflected by the analysis of modern engineering activity associated with the mining of minerals, excessive groundwater withdrawal, disposal of industrial and domestic wastes (including radioactive wastes) and their impacts on all components of the environment. Geology and Ecosystems includes a scientific approach to the complex monitoring of the environment under different natural and anthropogenic conditions, including the monitoring of permafrost regions. An important part of the book is the analysis of the "water factor" impact on ecosystems and sustainable development. Influences of intensive groundwater extraction on river flow, vegetation and land subsidence are also considered. This book is intended as a professional update for environmental scientists, analysts, environmental health care professionals, geologists, ecologists, hydrologists, and other professionals with an interest in the Earth's environments and with environmental protection.